The Digitalization Process of Manuscripts As Preservation And Salvage of Islamic Historical Information Sources In Aceh - Athaillah Khairunnisa, Clarence (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2025)
With over 10,000 Acehnese manuscripts dating back hundreds of years, there is a pressing need to address their vulnerability to damage and extinction. Additionally, there exists a risk of some manuscript owners wanting to sell these valuable artifacts abroad. Conservation and digitization have emerged as essential approaches to preserving these manuscripts. This research endeavors to safeguard Acehnese manuscripts by digitizing them, ensuring their accessibility and usability in a digital format for future generations. The primary objectives of this study are to outline the efforts employed to conserve ancient Acehnese manuscripts through digitization. This research adopts a descriptive qualitative methodology, utilizing observation, interviews, and documentation as data collection techniques. The findings of this study reveal the following: The preservation of ancient Acehnese manuscripts encompasses both physical methods such as conservation, restoration, and fumigation, as well as non-physical strategies through digitization employing tools like scanners, cameras, and gadgets